Prestasi Belajar IPS Terpadu Ditinjau dari Motivasi Belajar dan Lingkungan Sekolah Pada Siswa Kelas VIII Sekolah Menengah Pertama Muhammadiyah 10 Surakarta Tahun Ajaran 2014/2015 - Sari, Dewi Ratna, Drs. Sami'an, M.M (2015)
The purpose of this study were: 1) To determine the effect of learning motivation on learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah 10 Surakarta academic year 2014/2015. 2) To determine the influence of the school environment on learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah 10 Surakarta academic year 2014/2015. 3) To determine the effect of learning motivation and school environment on learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah 10 Surakarta academic year 2014/2015. Kuantitatf this associative study took place in 10 SMP Muhammadiyah Surakarta academic year 2014/2015. Take a sample of as many as 82 students. data collection techniques using the questionnaire technique. The data analysis technique used to test the hypothesis is multiple linear regression analysis, t test and F addition is done in the calculation of the coefficient of determination, the relative contribution and donations effectively. The conclusion of this study were: 1) There is a positive influence on learning motivation toward learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah Surakarta 10. It is shown from the results obtained t_hitung t test for learning motivation variable of 2.595> t_tabel amounted to 1,989 with effective contribution amounting to 10.60%. 2) There is a positive influence on the school environment on learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah Surakarta 10. It is shown from the results obtained t_hitung t test for school environment variables for 2,456> t_tabel amounted to 1,989 with the effective contribution of 9.7%. 3) There is a positive influence on learning motivation and school environment on learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah Surakarta 10. It is shown from the analysis results obtained F_hitung F test = 10.032> F_tabel = 3.15. The coefficient of determination 0.203. thereby indicating that the motivation to learn and the school environment together influence learning achievement IPS Integrated eighth grade students of SMP Muhammadiyah Surakarta 10 by 20.3% and the remaining 79.7% of learning achievement is influenced by other factors not examined in this study.